In-flight spatial disorientation induces roll reversal errors when using the attitude indicator. (November 2019) - Landman, Annemarie; Davies, Simon; Groen, Eric L.; van Paassen, M. M. (René); Lawson, Nicholas J.; Bronkhorst, Adelbert W.; Mulder, Max
Abstract: We hypothesized that an incorrect expectation due to spatial disorientation may induce roll reversal errors. To test this, an in-flight experiment was performed, in which forty non-pilots rolled wings level after receiving motion cues. A No-leans condition (subthreshold motion to a bank angle) was included, as well as a Leans-opposite condition (leans cues, opposite to the bank angle) and a Leans-level condition (leans cues, but level flight). The presence of leans cues led to an increase of the roll reversal error (RRE) rate by a factor of 2.6. There was no significant difference between the Leans-opposite and Leans-level condition. This suggests that the expectation strongly affects the occurrence of an RRE, and that people tend to base their responses on motion cues instead of on information on the AI. We conclude that expectation and spatial disorientation have a large effect on piloting errors and may cause hazardous aircraft upsets. Graphical abstract: Image 1 Highlights: Misleading in-flight motion cues were used to manipulate the participants' expectations about the aircraft bank angle. The results show that these cues are a significant determinant of expectation and roll reversal errors. Participants were more likely to prevent an error when they took more time to respond. Implications of the results are discussed on pilot training, simulation and research into upset recovery guidance systems.